Hazards in tunnelling and on falsework proceedings of the Third International Safety Conference held at the Institution of Civil Engineers, 19-20 March 1975 - Davis, Joyce S. (Institution of Civil Engineers, 1975)
The papers from this conference discuss structural safety and the Department of the Environment, British experiences of tunnel hazards and the trade unions' and the employers' contribution to safety. The Right Honourable Michael Foot provides the opening address.